Timing of symptomatic intracerebral hemorrhage after rt-PA treatment in ischemic stroke. Issue 4 (August 2019) - Chen, Patrick M.; Lehmann, Brittney; Meyer, Brett C.; Rapp, Karen; Hemmen, Thomas; Modir, Royya; Agrawal, Kunal; Hailey, Lovella; Mortin, Melissa; Meyer, Dawn M.
Abstract : Background: We investigated patterns in the time from recombinant tissue-type plasminogen activator (rt-PA) treatment to symptomatic intracranial hemorrhage (sICH) onset in acute ischemic stroke. Methods: We retrospectively reviewed all admitted "stroke code" patients from 2003 to 2017 at the University of California San Diego Medical Center from a prospective stroke registry. We selected patients that received IV rt-PA within 4.5 hours after onset/last known well and had sICH prehospital discharge. sICH diagnosis was made by prospective review. Endovascular-treated patients were excluded, given the variability of practice. sICH was prospectively defined as any new radiographic (CT/MRI) hemorrhage after rt-PA treatment and any worsened neurologic examination. Time to sICH was the time from rt-PA administration start to documented STAT head CT order time with the first evidence of new hemorrhage. Charts were reviewed for examination time metrics, demographics, clinical history, and neuroimaging. Results: sICH was identified in 28 rt-PA-only treated patients. The mean time to sICH was 18.28 hours (range 2.4–34 hours). Median time to sICH was 18.25 hours. sICH was correlated with increased age ( p = 0.02) and increased NIH Stroke Scale ( p = 0.01). Conclusions: Our findings suggest that rt-PA patients have the highest risk of post rt-PA sICH within the first 24 hours after treatment. This supports monitoring of rt-PA-treated patients in specialized settings such as neuro-intensive care units or stroke units. Our findings suggest that the probability of sICH is low 36 hours post rt-PA. Future larger studies are warranted to identify the patterns of bleeding after rt-PA administration.